THE ROLE OF THE PAWANG UTEN IN DISASTER MANAGEMENT (PERSPECTIVES ON ADAT GLE MAINTENANCE IN SERBAJADI SUBDISTRICT, ACEH TIMUR REGENCY) - Eva Andriani; Indra Indra; Nazli Ismail (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
This study aims to determine the effectiveness of the role of pawang uten in disaster management which includes exogenous latent variables, namely the adat gle maintenance while the endogenous latent variable is disaster management. To analyze the relationship between these variables, this study uses an analytical tool namely SmartPLS (Partial Least Square). Based on the results of the analysis and discussion of the research, it can be concluded that the role of pawang uten in adat gle maintenance it is in disaster management is yet to be seen. This is because the adat gle maintenance in Serbajadi Subdistrict only considered symbolic by the community when it will enter or manage the forest and internal responsibility for adat gle maintenance absolutely given to the pawang uten.